Pengaruh Profitabilitas, Ukuran Perusahaan, dan Kepemilikan Perusahaan Terhadap Kebijakan Dividen pada Perusahaan BUMN - Hidayat, Rifka Fauzia; Ulupui, I Gusti Ketut Agung; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
Examining and assessing the effects of company size, profitability, and institutional ownership on state-owned enterprises listed on the Indonesia Stock Exchange's dividend policy from 2018 to 2022 is the goal of this research. In this study, logistic regression analysis was utilized with the assistance of SPSS 29. Utilizing secondary data from corporate annual reports and financial reports that are available on each company's website as well as the IDX, this study is quantitative in nature. The study's population consists of the 24 state-owned companies that were listed on the Indonesian stock exchange between 2018 and 2022. In this study, 75 data samples from 15 businesses that complied with the criteria were used to implement purposeful sampling. The results of the study indicate that, at least in part, profitability has a considerable favorable influence on the dividend policy. The company's size has no discernible effect on the dividend policy. Institutional ownership has no appreciable effect on the dividend policy. The study's implication for the corporation is that it should maximise profits through improved performance, particularly when it comes to the utilisation of company assets. Investors might therefore infer from this that they can base their selections on profitability. This is due to the study's showing that dividend policy can be impacted by a company's profitability.